2021
DOI: 10.1149/1945-7111/abde7e
|View full text |Cite
|
Sign up to set email alerts
|

Size-Controllable Strategy of ZnO Micro/Nanorods for Electrochemical Detection of H2O2

Abstract: An electrochemical sensor was promoted for the rapid and efficient detection of hydrogen peroxide via the ZnO nano/microrods-based (GCE) electrode. The ZnO nano/microrods were controllable prepared by changing zinc precursor under hydrothermal condition and the sensing properties of ZnO materials were studied. The sensing performance was optimized by adjusting ZnO’s morphologies and size. The ZnO nanorods (ZNRs)-based electrode exhibits a notable sensing response toward hydrogen peroxide compared to other modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
6
1
Order By: Relevance
“…A brief literature comparison from recently published papers revealed that the values obtained for the sensitivity in the present samples were superior to most of those reported for ZnO-based electrodes [117][118][119][120]. Regarding the LOD, values in the µM range can already be attained for ZnO composites with noble metals or mesoporous carbon [117][118][119]. Nevertheless, the here estimated LODs are well in line with the ones required for glucose sensing, for instance, indicating the suitability of these materials to be used as transducers in further biosensing applications.…”
Section: H 2 O 2 Sensing Via Pl and CVcontrasting
confidence: 82%
See 2 more Smart Citations
“…A brief literature comparison from recently published papers revealed that the values obtained for the sensitivity in the present samples were superior to most of those reported for ZnO-based electrodes [117][118][119][120]. Regarding the LOD, values in the µM range can already be attained for ZnO composites with noble metals or mesoporous carbon [117][118][119]. Nevertheless, the here estimated LODs are well in line with the ones required for glucose sensing, for instance, indicating the suitability of these materials to be used as transducers in further biosensing applications.…”
Section: H 2 O 2 Sensing Via Pl and CVcontrasting
confidence: 82%
“…Table 2 displays a summary of the sensing figures of merit for the here studied sensors, as well as a comparison with those reported in the literature for ZnO-based H 2 O 2 sensors. As above-mentioned, PL sensing is scarcely used in this type of sensor, whereas transduction via electrochemical assessment using ZnO and ZnO-based composites is far more common [113][114][115][116][117][118][119]. A brief literature comparison from recently published papers revealed that the values obtained for the sensitivity in the present samples were superior to most of those reported for ZnO-based electrodes [117][118][119][120].…”
Section: H 2 O 2 Sensing Via Pl and CVmentioning
confidence: 60%
See 1 more Smart Citation
“…The ZnO/BiOCl materials‐based working electrode (GCE) with Pt and SCE electrode was immersed into a beaker containing 30 mL of 0.1 M PBS (pH=7.4). The working electrode coated with ZnO/BiOCl sample and the electrode preparation processes are shown in our previous report [9,36] . To test the sensing properties, different amounts of ammonia were added to the PBS solution in a sequential order.…”
Section: Methodsmentioning
confidence: 99%
“…The working electrode coated with ZnO/BiOCl sample and the electrode preparation processes are shown in our previous report. [9,36] To test the sensing properties, different amounts of ammonia were added to the PBS solution in a sequential order. The ammonia sensing analysis was studied using cyclic voltammetry (CV) and linear sweep voltammetry (LSV).…”
Section: Preparation Of Biocl Nanosheetsmentioning
confidence: 99%